Physics of superconductors - Bennemann, K. H.; Ketterson, J. B. (Berlin: Springer-Verlag, 2004)
This is the second volume of a comprehensive two-volume treatise on superconductivity that represents the first such publication since the earlier widely acclaimed books by R. Parks. It systematically reviews the basic physics and recent advances in the field. Leading researchers describe the state of the art in conventional phonon-induced superconductivity, high-Tc superconductivity, and in novel superconductivity, including triplet pairing in the ruthenates. The second volume is largely concerned with novel superconductors, such as heavy-fermion metals and organic materials, and also includes granular superconductors. Important new results on current problems are presented in a manner designed to stimulate further research. Numerous illustrations, diagrams and tables make this book especially useful as a reference work for students, teachers and researchers.
Includes bibliographical references.; Index 1115-1140p.
Keywords: Superconductivity; Superconductors; Physics